Pengembangan Perangkat Lunak Payment Remainder di Universitas Bina Darma - Nodi Setiawan; Merry Agustina (APTIKOM SUMSEL, 2020)
The development of technology has a very important role in all types of human activities such as work, play, and search for information that is currently up to date, like Telegram is a software that uses computer assistance and utilizes cellular technology that is integrated to distribute messages that are integrated through information systems through the media. Bina Darma University has a payment system of tuition in installments, but there are some students who forget to pay off the remaining payments. therefore, an application is needed that can remind students of their payments. To be able to run this software, a Telegram API is needed that has been synchronized with the Telegram Bot service, therefore a software that can send broadcase messages to all students of Bina Darma University through the Telegram application